AKIBAT HUKUM PEMBATALAN PERJANJIAN BOT (BUILD OPERATE TRANSFER) YANG DIBATALKAN SECARA SEPIHAK OLEH PEMEGANG HAK ATAS TANAH (STUDI KASUS : PUTUSAN N0. 97/PK/PDT/2017) - Vanny Aryanti; Siti Nurbaiti (Jurnal Hukum Adigama, 2018)
The investment activity has grown up rapidly in Indonesia. Indonesia needs to do some infrastructure developments. The goverments offers one of the investment to their people, in form of Build Operate Transfer Contract. Under a Build Operate Transfer Contract, an entity ussually a goverment grants a concenssion to a private company to finance, build, and operate a project. The private company usually operates the project for a time periode with the goal of recouping its investment, then transfers control of the project to the goverment. In Fact some contracts has been cancelled by one side, the landlord. One of them is the contract between PT Sarana Pembangunan Palembang Jaya and PT Tradeways International. The landlord accuses the investor to do his obligations without good intentions.This research method is normative. Impact form tort whose done by the landlord with using secondary data source and primary, secondary, and tertiary legal source. However, the cancellation of the contract by one side has not fulfilled all the elements that is containin Article 1266 Indonesian Civil Code. The consequences behind that is the landlord must pay the compensations.